Health promotion in the integration of newly arrived migrants in northern Sweden - Svanholm, Sara (Mittuniversitetet, Institutionen för hälsovetenskaper (HOV), 2022)
Background: Migrants, especially forced migrants, have an increased risk of ill health. Having a structural focus on health is crucial for battling health inequities. Actors outside the healthcare services are important to promote health, and both policy and political context are thus key to promoting the health of newly arrived migrants in Sweden. The aim of this thesis was to explore approaches to health promotion within the multi-level governance of the integration of newly arrived migrants in northern Sweden. Methods: Different methods of data collection and analysis were used in the thesis. For Study I, policies relevant to Sweden’s Establishment Program were analyzed using discourse analysis. For Studies II and III, a questionnaire on politicians’ views on their roles, responsibilities, and possibilities to promote the health of newly arrived migrants was created based on interviews with politicians. In total, 667 politicians answered the questionnaire, and both bivariate and multivariate analyses were used. For Study IV, a secondary analysis of focus group interviews was performed. The interview transcripts were analyzed using content analysis. Finally, Study V consists of interviews with civic communicators who work within the civic orientation for newly arrived migrants in Sweden. Thematic analysis was used to analyze the transcribed interviews. Results: The policy documents that described the Establishment Program in Sweden contained no explicit definition of health. The discourses of health showed a medicalized and individualized view of health, where ill health was considered a risk (Study I). Politicians more often considered health effects for the general population as a whole, rather than for newly arrived migrants specifically. Factors contributing to whether they considered health effects for newly arrived migrants included self-rated knowledge, attitude, being female, and having previous experience working in public health (Study II). Further, politicians rated societal responsibility and the ...